When the Mystics Embrace Love: Comparing the Insights of Yunus Emre and Jacopone da Todi - Robby Igusti Chandra (Cipanas Theological Seminary, 2023)
Many studies on Yunus Emre, a Turkish Sufi and Jacopone da Todi, an Italian Franciscan, focus on their views of mystical love, especially concerning mystical union, however, the term ”love” that both use needs more exploration This study explores the question of whether their views of love have more similarities or differences by comparing the aspects of love, the center of love and its origin, and the end of the journey in love. Through thematic analysis, the results show that both conveyed a similar view about love, its origin, and the union with God as the destination of love. However, although they similarly view love as centered on God, their views of God show differences. Jacopone focuses on Christ as God who embraces pain and suffering, while Yunus is more apophatic in his insight into God. The finding might help the readers to appreciate various spiritual expressions in modern societies and to delve deeper into each of their core faith.